(untitled) (Bangladesh Journal of Medical Biochemistry, 2018)
Diabetes is characterized by hyperglycaemia with alterations of lipid parameters. The effects of Aloe vera (A.V) gel extract on lipid profiles of streptozotocin-induced diabetic rats were investigated. Seventy-two male albino rats were randomly divided into six groups of 12 rats each; control, diabetic control, 4 ml/kg and 8 ml/kg body weight (b.w.) A.V, 10 mg/kg b.w. glibenclimide and non-diabetic 8 ml/kg b.w. A.V groups. They were treated for 14 and 28 days. The plasma and HDL lipid profiles (triacylglycerols, cholesterol and phospholipids) of the diabetic rats were significantly (p<0.05) increased, while those of the VLDL+LDL, RBC, RBC membrane and organs were observed to be significantly (p<0.05) reduced, when compared to the control after 14 and 28 days of treatment. A.V gel extract significantly (p<0.05) ameliorated the disruptions observed in the lipid profiles of the diabetic and thus provide a scientific rationale for the use of Aloe vera as a therapeutic agent. Bangladesh J Med Biochem 2016; 9(1): 11-26